ANALISIS HUBUNGAN KAUSALITAS JUMLAH UANG BEREDAR DAN DEFISIT ANGGARAN TERHADAP INFLASI DI INDONESIA PADA TAHUN 2002-2017 - Ayu Melia Astuti; Anthony Mayes; Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine whether there is a significant reciprocal relationship between the money supply and the budget deficit against inflation in Indonesia in 2002-2017. This study uses time series data periodically during the period 2002 to 2017. In this study using the method of quantitative analysis using econometric model, VAR (Vector Auto Regression). This research uses Eviews 7.0 analysis tool. Unit roots test results show that the money supply, budget deficit and non-stasionary rate at the level, but money supply data, budget deficit and stationary inflation at first difference level. The cointegration test results show that the relationship between the money supply, budget deficit and inflation in Indonesia has no long-run equilibrium relationship. Granger Causality Test results show that there is a causality relationship between the money supply to inflation, but there is no causality relationship between budget deficit and money supply as well as inflation and budget deficit, Implementation Response Function Based on the results, it is found that the money supply has a negative effect against inflation. While the result of variance decomposition shows that the role of money supply, budget deficit and significant inflation.Keywords : money supply, defisit budget, inflation